Multiplex PCR assay for simultaneous detection of Phytophthora, Pythium and Fusarium associated with foot rot and yellowing diseases of black pepper: Multiple PCR for the detection of pathogens infecting black pepper - Jeevalatha, A; Zumaila, Fathimath; Biju, C N; Peeran, Mohammed Faisal (Journal of Spices and Aromatic Crops, 2022)
In this study, a multiplex PCR assay was developed to detect Phytophthora, Pythium and Fusarium infecting black pepper. Genus-specific primers were designed from the conserved region of ITS and a multiplex PCR was optimized by manipulating the annealing temperature and primer as well as MgCl2 concentrations. The black pepper 18S rRNA gene-specific primers were also included in the multiplex PCR assay as internal control. The assay successfully detected the pathogens from artificially inoculated black pepper roots and did not show any cross amplification with other fungal pathogens of black pepper such as Rhizoctonia solani, Sclerotium rolfsii and Colletotrichum sp. Hence, the developed multiplex PCR assay will help in early diagnosis of the cause of black pepper yellowing leading to timely adoption of management strategies.